2014
DOI: 10.3126/jcmc.v4i2.10857
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographically detected renal fusion anomalies in Western Region of Nepal

Abstract: To establish the incidence and patterns of renal fusion anomalies based on Ultrasonography (USG) in Western region of Nepal. In 2 years period, patients undergoing abdominal USG at Gandaki Medical College between 2010 and 2012 were screened for renal fusion anomalies. After identification, incidence and male:female ratio were stratified for total renal fusion anomalies, horseshoe kidney, crossed fused ectopia and fused pelvic kidney. Out of 31498 patients who underwent abdominal USG, there were 71(1:444) cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The gender ratio was also high with 6 males to 1 female and similar such observation was reported by others also [17]. In contrast, an ultrasonographic study from Nepal has reported an incidence of 1 in 516 (61 horseshoe kidneys out of 31498 patients screened, 0.2%) with male to female ratio of 1:2 (20 males.41 females) which is just the reverse of ratio reported in the literature and this could be due to more number of females undergoing ultrasonography [19].…”
Section: Discussionsupporting
confidence: 79%
“…The gender ratio was also high with 6 males to 1 female and similar such observation was reported by others also [17]. In contrast, an ultrasonographic study from Nepal has reported an incidence of 1 in 516 (61 horseshoe kidneys out of 31498 patients screened, 0.2%) with male to female ratio of 1:2 (20 males.41 females) which is just the reverse of ratio reported in the literature and this could be due to more number of females undergoing ultrasonography [19].…”
Section: Discussionsupporting
confidence: 79%
“…There are 98 public schools and 121 private schools in the Chitwan district. 28 However, no organized attempt has been made to collect data on the teachers' health issues in relation to their voice. This can lead to underdiagnosis of the problem and lack of timely intervention.…”
Section: Discussionmentioning
confidence: 99%